2012
DOI: 10.1186/1471-2105-13-274
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative genetic and epigenetic model of complex traits

Abstract: BackgroundDespite our increasing recognition of the mechanisms that specify and propagate epigenetic states of gene expression, the pattern of how epigenetic modifications contribute to the overall genetic variation of a phenotypic trait remains largely elusive.ResultsWe construct a quantitative model to explore the effect of epigenetic modifications that occur at specific rates on the genome. This model, derived from, but beyond, the traditional quantitative genetic theory that is founded on Mendel’s laws, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Although this has helped greatly to improve our understanding of the origin of epigenetic alterations, a systematic detection of this phenomenon through GWAS in a commonly used case-control design is still not largely feasible [19]. Here, we have integrated quantitative genetic and epigenetic principles established by Wang et al [18] into a case-control setting, allowing the significance of genetic and epigenetic effects on a disease to be tested and analyzed. In the previous studies, quantitative genetic principles were incorporated with a case-control design to analyze the associations between epistasis and disease [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this has helped greatly to improve our understanding of the origin of epigenetic alterations, a systematic detection of this phenomenon through GWAS in a commonly used case-control design is still not largely feasible [19]. Here, we have integrated quantitative genetic and epigenetic principles established by Wang et al [18] into a case-control setting, allowing the significance of genetic and epigenetic effects on a disease to be tested and analyzed. In the previous studies, quantitative genetic principles were incorporated with a case-control design to analyze the associations between epistasis and disease [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…By making crosses derived from epigenomically perturbed isogenic lines, Johannes and Colome-Tatche [17] developed an approach to estimating epigenetic variation, allowing the effects of epiallelic instability, recombination, parent-oforigin effects and transgressive segregation to be characterized. Wang et al [18] integrated conventional quantitative genetic theory with DNA methylation mechanisms to provide an approach for quantifying epigenetic effects and variation in complex traits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential role of epigenetics on complex traits has led to studies of the impact of epigenetic variation on phenotypic and genetic variations. For example, in a recent in silico study, it was shown that epigenetic modification of one allele at a biallelic locus can result in an 11 % of total genetic variance attributed to epigenetic variation at moderate allele frequency even if u , the epigenetic modification rate, is as low as 0.01 [ 21 ]. The proportion of genetic variance explained by epigenetic variation could be as large as 18 % if u increases to 0.5.…”
Section: Contribution Of Imprinting To Genetic Variationmentioning
confidence: 99%
“…The ratio defines the proportion of total genetic variance explained by imprinting. This ratio is, to some extent, equivalent to the definition of in [ 21 ], with the only difference being that these authors were interested in a broader concept of epigenetic mechanism while here we are interested in imprinting only. We graphically illustrate how imprinting can impact the evaluation of marked variance, and its consequences if ignored.…”
Section: Contribution Of Imprinting To Genetic Variationmentioning
confidence: 99%